Edukasi Gizi Seimbang pada Remaja dalam Upaya Pencegahan Stunting - Novi Maya Sari; Sandra Ilona; Afrah Diba Faisal; Rahmi Melfa Widodo (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2026)
This community service activity aimed to improve adolescents’ knowledge and awareness of balanced nutrition as an effort to prevent stunting from an early age. The program targeted 100 female students at SMA Negeri 13 Padang, who were selected due to their higher risk of anemia and their important role in preventing stunting in future generations. The implementation method consisted of four stages: program socialization, a pre-test to assess participants’ initial knowledge, interactive health education using presentations and leaflets on balanced nutrition, clean and healthy living behaviors, and the distribution of iron supplementation tablets, followed by a post-test evaluation. The results showed an increase in participants’ knowledge regarding stunting prevention and balanced nutrition. Most participants demonstrated a good level of knowledge (87%) and a positive attitude toward stunting prevention (68%). However, behavioral changes were not yet fully optimal, with the majority of participants still categorized at a moderate level. In conclusion, balanced nutrition education was effective in improving adolescents’ knowledge and attitudes toward stunting prevention. Therefore, continuous implementation through school support and adolescent health programs is necessary to achieve sustainable behavioral change.